2007
DOI: 10.1002/eji.200636771
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous or Mycobacterium tuberculosis‐induced apoptotic neutrophils exert opposite effects on the dendritic cell‐mediated immune response

Abstract: Polymorphonuclear neutrophils (PMN) modulate the adaptive immune response through interactions with immature dendritic cells (iDC) while spontaneous apoptotic neutrophils (PMNapo) may have an inhibitory effect on DC functions. We investigate the effect exerted by PMNapo in DC maturation and the role of Mycobacterium tuberculosis (Mtb)-induced PMNapo in the cross-presentation of mycobacterial antigens. We demonstrate that Mtb triggers the maturation of iDC while it is impaired by the presence of PMNapo, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…They may also be able to acquire antigens from apoptotic vesicles as demonstrated for macrophages [45]. More detailed analysis of the contribution of live and apoptotic neutrophils to this cross-presentation is required [46]. Whatever the mechanism, these data clearly demonstrate that neutrophils could help DC to cross-present BCG antigens to naive CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 79%
“…They may also be able to acquire antigens from apoptotic vesicles as demonstrated for macrophages [45]. More detailed analysis of the contribution of live and apoptotic neutrophils to this cross-presentation is required [46]. Whatever the mechanism, these data clearly demonstrate that neutrophils could help DC to cross-present BCG antigens to naive CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 79%
“…Neutrophil activity may modify DC maturation and activation (64)(65)(66) and enhance the release of IL-12 and TNF-a from DCs (65), suggesting that neutrophil responses play a crucial role in influencing DCs to induce Th1 responses upon contact with T cells. Furthermore, neutrophils can present Ag to T cells and induce T cell proliferation and cytokine release (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that PMN Mtb trigger a cell-cell contactdependent DC maturation, whereas PMN Apo is inhibitory for DC maturation and could play a important part in maintaining peripheral tolerance [35,36]. Both PMN Apo and PMN Mtb interacted with DCs, but only a few cells were actually internalized by DCs, a finding supported by the observation that apoptotic PMNs are phagocytosed only when presented to the IDCs in vast excess [10].…”
Section: Upon Activation Pmns Recruit Immune Cells Such As T-cells Andmentioning
confidence: 53%